PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN : (STUDI KASUS : PT. BANK NEGARA INDONESIA,TBK KANTOR CABANG MAKASSAR) - Rahman, Zainuddin (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
This study aims to identify how Leadership Style and Organizational Culture influence employee performance. It is conducted quantitatively using a survey method. The population studied consists of employees at the Makassar Branch Office of PT. Bank Negara Indonesia (Persero) tbk, with a sample size of 55 respondents. The analytical methods include tests for normality, multicollinearity, heteroskedasticity, and multiple linear regression analysis. The research findings indicate that both Leadership Style and Organizational Culture have a positive and significant combined influence on employee performance. These findings have important implications for decision-making concerning employee development.